LIVING FIQH AS SOCIAL DYNAMICS: A STUDY OF THE ACTUALIZATION OF FIQH OF CIVILIZATION IN PONDOK PESANTREN DARUL ULUM, BANDUNG, TULUNGAGUNG. - Mashuri, Mashuri (UIN Sayyid Ali Rahmatullah Tulungagung, 2025)
This study aims to examine the actualization of living fiqh of civilization in the dynamics of social religion in the Pondok Pesantren Darul Ulum Bandung, Tulungagung. This study departs from the awareness of the importance of transforming fiqh from normative discourse into adaptive and contextual social praxis, especially in the midst of increasingly complex social changes. Through a qualitative approach and case study method, this study explores in depth the values, practice patterns, and strategies for implementing fiqh of civilization in pesantren as a response to contemporary challenges. The results of the study show that Darul Ulum Islamic Boarding School practices fiqh that is not only based on text, but also considers social reality with the maqashid shari’ah approach. The developed fiqh is moderate, inclusive, and solutive to various community problems, such as issues of social justice, health, environment, and cultural pluralism. Pesantren play a strategic role as value producers and agents of social transformation that make fiqh a dynamic guide to life. The implementation of living fiqh in this pesantren can be seen in the integration of a curriculum that is responsive to contemporary issues, the involvement of santri in community empowerment activities, and collective awareness of the importance of building an Islamic civilization that is rahmatan lil 'alamin. Thus, this research confirms that the living fiqh of civilization developed by Darul Ulum Islamic Boarding School is not only a renewal of Islamic thought, but also a concrete form of fiqh that lives in society and contributes significantly to equitable and sustainable social development.